Rocket‐borne measurements of electron temperature and density with the Electron Retarding Potential Analyzer instrument. Issue 7 (4th July 2016) - Cohen, I. J.; Widholm, M.; Lessard, M. R.; Riley, P.; Heavisides, J.; Moen, J. I.; Clausen, L. B. N.; Bekkeng, T. A.
Abstract: Determining electron temperature in the ionosphere is a fundamentally important measurement for space science. Obtaining measurements of electron temperatures at high altitudes (>700 km) is difficult because of limitations on ground‐based radar and classic spacecraft instrumentation. In light of these limitations, the rocket‐borne Electron Retarding Potential Analyzer (ERPA) was developed to allow for accurate in situ measurement of ionospheric electron temperature with a simple and low‐resource instrument. The compact ERPA, a traditional retarding potential analyzer with multiple baffle collimators, allows for a straightforward calculation of electron temperature. Since its first mission in 2004, it has amassed significant flight heritage and obtained data used in multiple studies investigating a myriad of phenomena related to magnetosphere‐ionosphere coupling. In addition to highlighting the scientific contributions of the ERPA instrument, this paper outlines its theory and operation, the methodology used to obtain electron temperature measurements, and a comparative study suggesting that the ERPA can also provide electron density measurements. Key Points: The ERPA instrument makes in situ thermal electron temperature measurements The ERPA has proven reliable on over a decade of sounding rocket missions The ERPA can also make measurements of electron density and approximate the payload potential